Fatty Acid Enrichment of Corn Extrudates with Hemp Seeds - Marta Igual; David Gimeno; Purificación García-Segovia; Javier Martínez-Monzó; Juliana Navarro-Rocha (Molecules)
Hemp seeds (HSs) are a rich source of essential fatty acids, proteins, and antioxidant compounds, making them an attractive ingredient for the food industry. This work studies the viability of enriching corn extrudates with hemp seeds, specifically to improve their fatty acid profile and phenolic content, thereby enhancing the nutritional value of the snack. Extrudate formulations with different concentrations of HSs (up to 12.5%) were evaluated, and the physicochemical, textural, and antioxidant properties of the resulting products were analyzed. The results showed that increasing the HS concentration improved the lipid profile of the products, raising the content of unsaturated fatty acids to 75.6% in the snack fortified with 12.5% of HSs and lowering the proportion of saturated fatty acids. This may reduce the risk of cardiovascular diseases compared with corn extrudates. The total phenolic content of the snacks and their antioxidant capacity also increased linearly with the increase of HSs in the formulation. A reduction in specific mechanical energy during extrusion was also observed, attributed to the higher fat content, which facilitates the lubrication of the process. At the physicochemical level, the HS-enriched snacks showed improvements in texture. These snacks were softer, reducing the hardness of the corn snack while maintaining crunchiness. They were even more stable due to a lower water content. The fortification of snacks with hemp seeds provides consumers with a healthier option, while maintaining the appealing crunchy texture and visual appearance regardless of some changes in their color attributes.